Polarization, candidate positioning, and political participation in the U.S. (October 2021) - Simas, Elizabeth N.; Ozer, Adam L.
Abstract: Although there is clear evidence of growing ideological divides between the Democratic and Republican Parties, there is a lack of consensus about how this polarization impacts political participation. Using data from the 2010–2018 election cycles, we test how candidates' distances from each other and distances from constituents are related to both voting and non-voting behavior. We fail to find evidence that the distance between candidates in and of itself depresses activity. Distance from a copartisan candidate can lower the likelihood of participation, but this is often offset by the greater likelihood of participation that comes with increased distance from an outparty candidate. Together, these results suggest that rather than demobilizing potential voters, polarization is instead motivating individuals by clarifying which candidate they do not want. Such findings are consistent with evidence of significant levels of negative partisanship and offer further insight into how candidate positioning impacts the electorate.